Giant colonic diverticulum—a rare cause of acute abdomen. Issue 2 (7th February 2018) - Syllaios, Athanasios; Daskalopoulou, Dimitra; Bourganos, Nikolaos; Papakonstantinou, Anastasia; Triantafyllou, Evangelia; Koutras, Antonios; Georgiou, Christos
Abstract: Giant colonic diverticulum (GCD), defined as diverticulum larger than 4 cm, is a rare entity. It is generally a manifestation of colonic diverticular disease and can have dramatic complications such as perforation, abscess, volvulus, infarction and adenocarcinoma. This report documents the case of a 63-year-old man coming to the Emergency Department with acute abdomen due to a perforation of a GCD. In the plain abdominal X-ray the 'Balloon-sign' was revealed, computed tomography scan and Hartmann's procedure were performed. Acute abdomen can occur as a manifestation of a complication of a GCD, and this report highlights the fact that GCD should be considered for patients with a high risk of diverticular disease and abdominal pain.